2020
DOI: 10.1177/09726225211007247
|View full text |Cite
|
Sign up to set email alerts
|

Driving Employee Engagement Through Five Personality Traits: An Exploratory Study

Abstract: An attempt has been tried to explore the personality factors in predicting employee engagement among the middle-level employees in the IT industry. Based on an empirical investigation of 383 middle-level employees working in IT firms, the researcher cognizes their perception of various personality-related factors extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience. The present study was exploratory in nature. A variance-based structural equation model (SEM) approach was adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
(79 reference statements)
0
1
1
Order By: Relevance
“…This is explained by the lack of social interaction and the lack of clear structure when working remotely. This finding contradicts that of traditional workplace where extraversion and conscientiousness are significant predictors of employee engagement (Ansari, 2020).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This is explained by the lack of social interaction and the lack of clear structure when working remotely. This finding contradicts that of traditional workplace where extraversion and conscientiousness are significant predictors of employee engagement (Ansari, 2020).…”
Section: Discussioncontrasting
confidence: 76%
“…Perceived organizational support also includes support for training and learning opportunities, which were positively linked with employee engagement (Lee et al , 2017) and employee performance (Arwab et al , 2022b). Research also indicated a positive relationship between the five personality traits and employee engagement, including extraversion, conscientiousness, neuroticism and openness to experience (Ansari, 2020). In addition, existing literature indicated three types of related psychological conditions: psychological meaningfulness, psychological safety and psychological availability (Saks and Gruman, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the results did not support a positive association between conscientiousness and vigor (H7), which is surprising. Second, the results suggest that conscientiousness and openness to experience are positively related to dedication and absorption (H3 and H14), and these are consistent with the literature [1,9,10,31,40,[45][46][47] . Third, the results provide empirical evidence in support of the negative association of neuroticism with dedication (H11) but the diametrically opposite effect concerning vigor and absorption (H10 and H12).…”
Section: Discussionsupporting
confidence: 87%
“…In a recent study on 152 employees of small and medium-sized organizations in Bosnia, the researchers found that extroverted individuals showed higher levels of work engagement [30] . A recent study conducted on 383 employees in the information technology sector in India found that extraversion was positively associated with work engagement [31] . Extraverted people enjoy working and do not get tired; they continue to work till the work is done (vigor).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation